Floristic composition and economic value of trees at agroforestry parak in Tanjung Raya District, Agam Regency, West Sumatra Indonesia - Alfitrah Habibullah. M; Irma Leilani eka Putri; Azwir Anhar; Reki Kardiman (Bioscience, 2024)
This study aimed to investigate the floristic composition and the economic values of trees at the agroforestry parak in Maninjau, Tanjung Raya District. Four different villages were selected purposively according to the tree structure of parak, and each village represented each compass point surrounding the Maninjau Lake. 20 x 100 m plot was established at each sites, where all tree species were identified, and five owner of the parak at each location were asked about the fruiting and harvesting season, management and potential income from each of tree species. 20 tree species belong to 13 families were found across the sites, but only five were occured at all sites, while the others were missed at least from one site. Most species produced fruits with fruiting and harvesting season ranged from one to three times a year, but only seven species knew the income from selling the commodity. From all seven species, which varied on the harvesting season, the owner of each parak gained up to four million IDR per month. This study showed that variation of species and the harvesting season beneficial the owner of the parak and may kept the parak as primary or alternative livelihood.